The Role of Community Participation In Sustainability Water Resources Management in Malang District - Muniah Muniah; Soemarno Soemarno; Nuddin Harahab (The Indonesian Green Technology Journal, 2019)
Strategies that aims to assist the availability of clean water in Sumberejo Village, Pagak District, Malang Regency through community participation supported by PAMSIMAS program (Community-Based Water Supply and Sanitation). Sustainability on the factors of community participation supports the availability of clean water. These factors include namely thinking, skills or expertise, energy, and funding. In this study, we found that community participation is an effective strategy to develop the governance of sustainable rural health. This research was conducted from October to December 2016 with a method of explanation of the questionnaire by purposive sampling, Slovin method with probability sampling technique with a type of proportionate random sampling. In this study also explained the characteristics of the community which included gender, age of the respondent, occupation. The results of the study state that the factors that influence the sustainability of the availability of clean water are of significant value. Of these factors the highest value is on the funding factor. This study has important implications for conceptualizing the role of community participation in maintaining PAMSIMAS program and to the sustainability of the water supply.Keywords: Sustainability, Water, Participation, PAMSIMAS, Funding